ERGONOMIC ANALYSIS OF TRANSMISSION OVERHAUL PRACTICES WITH THE RULA METHOD IN THE DEPARTMENT MECHANICAL ENGINEERING EDUCATION - Ramdhani, Ramdhani; Peranginangin, Excellent Demolka (Universitas Pendidikan Indonesia, 2022)
This research was conducted to determine the work posture and the level of ergonomics risk in the transmission overhaul practice activity which later resulted in recommendations for designing ergonomic practical tools based on anthropometry of students from the Department of Mechanical Engineering Education UPI. Descriptive method through a cross-sectoral approach is used to answer the objectives of this study. Instruments such as anthropometric questionnaires regarding the dimensions of student body measurements include data on upright height, length of arm span to the side, and length of arm forward. The Rapid Upper Limb Assessment (RULA) questionnaire was also used for ergonomic risk level data requirements. The data that has been obtained is then processed by means of a data uniformity test, data adequacy test, and percentile calculation to determine 3 students who represent body size at the 5th, 50th, and 95th percentiles and continue to practice transmission overhaul which will be observed through a questionnaire. The results of data processing in this study explained that students' unusual work postures such as the neck upturned, legs bent, and the position of the hands reaching upwards for a long enough duration to cause aches and pains after the practice was over. This is evidenced by the acquisition of an overall score of 7 which means it is necessary to investigate and make changes to the process as well as the tools used in the transmission overhaul practice.